2011
DOI: 10.1075/rcl.9.1.10cre
|View full text |Cite
|
Sign up to set email alerts
|

Euphemistic conceptual metaphors in epitaphs from Highgate Cemetery

Abstract: Death is a timeless taboo in which psychological, religious and social interdictions coexist. In consequence, human beings feel reluctant to deal with the subject of death using straightforward terms and therefore tend to soften the effect of what they really wish to communicate. With this in mind, it is the aim of this paper to explore the euphemistic language on a sample of epitaphs from the Eastern Highgate Cemetery in London. As figurative language constitutes a potent source for death-related euphemism, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Eliecer Crespo Fernández (2011) observed that due to the taboo nature of death, epitaphs inscribed on funerary monuments are purposefully euphemistic and poetic, to avoid straightforward language. He explored a sample of 160 epitaphs from Highgate Cemetery East and conceptually mapped a number of metaphors which he crystallized around six themes;DEATH IS A JOURNEY .…”
Section: Creative Space and Cultural Capitalmentioning
confidence: 99%
See 4 more Smart Citations
“…Eliecer Crespo Fernández (2011) observed that due to the taboo nature of death, epitaphs inscribed on funerary monuments are purposefully euphemistic and poetic, to avoid straightforward language. He explored a sample of 160 epitaphs from Highgate Cemetery East and conceptually mapped a number of metaphors which he crystallized around six themes;DEATH IS A JOURNEY .…”
Section: Creative Space and Cultural Capitalmentioning
confidence: 99%
“…The small grave of baby Louis Ingram (October-December, 2007) with a small teddy bear and several tiny Matchbox Cars displays tragedy and loss through the epitaph, “We loved you enough for a lifetime.” Adjacent to the grave of my great uncle, a friend has created a memorial on the seat which was erected alongside. 9 This is adorned with a display of metallic Soviet badges which have been glued in line suggesting medals, probably totems to highlight solidarity with revolutionary communist ideals (and countercultural capital), unlike the six themes mentioned by Crespo Fernández (2011).…”
Section: Creative Space and Cultural Capitalmentioning
confidence: 99%
See 3 more Smart Citations